Research on the sustainable efficacy of g-MoS2 decorated biochar nanocomposites for removing tetracycline hydrochloride from antibiotic-polluted aqueous solution - Zeng, Zhuotong; Ye, Shujing; Wu, Haipeng; Xiao, Rong; Zeng, Guangming; Liang, Jie; Zhang, Chang; Yu, Jiangfang; Fang, Yilong; Song, Biao (The Science of the total environment, 2019)
Antibiotic concentrations in surface waters far exceed the pollution limit due to the abuse of pharmaceuticals, resulting in an urgent need for an approach with potential efficiency, sustainability and eco-friendliness to remove antibiotic pollutants. A novel biochar-based nanomaterial was synthesized by hydrothermal synthesis and was investigated for its removal potential for tetracycline hydrochloride (TC) from both artificial and real wastewater. The associative facilitation between biochar and g-MoS2 nanosheets was proposed, revealing the favorable surface structures and adsorption properties of the composite. The related adsorption kinetics, isotherms and thermodynamics were studied by several models with adsorption experimental data, turning out that biochar decorated by g-MoS2 exhibited optimum TC removal with adsorption capacity up to 249.45 mg/g at 298 K. The adsorption behavior of TC molecules on g-MoS2-BC can be interpreted well by three-step process, and it is dominated by several mechanisms containing pore-filling, electrostatic force, hydrogen bond and π-π interaction. In addition, the cost-effective g-MoS2-BC nanocomposites demonstrated excellent adsorption and recycling performance in TC-contaminated river water, which might provide the underlying insights needed to guide the design of promising approach for contaminant removal on a large scale in practical application. [Display omitted] •Hierarchical g-MoS2 nanosheets were successfully loaded onto the surface of biochar.•Pore structures and surface properties of biochar were improved by decorated with g-MoS2.•Sustainable efficient removal for TC by novel g-MoS2-biochar nanocomposite was confirmed.•Several mechanisms participated in the antibiotic removal were also discussed.•Further research focuses on the catalytic degradation ability of nanocomposite for its regeneration.